Calculați :
![3(5 \sqrt{2} - 6 \sqrt{2} ) - (13 \sqrt{2} - 8 \sqrt{2} ) 3(5 \sqrt{2} - 6 \sqrt{2} ) - (13 \sqrt{2} - 8 \sqrt{2} )](https://tex.z-dn.net/?f=3%285+%5Csqrt%7B2%7D++-+6+%5Csqrt%7B2%7D+%29+-+%2813+%5Csqrt%7B2%7D++-+8+%5Csqrt%7B2%7D+%29)
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
Explicație pas cu pas:
3[√2(5-6)]-[√2(13-8)]=
=3(-1√2)-(5√2)=
= -3√2-5√2=
=-8√2
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă